2015
DOI: 10.1128/genomea.00684-15
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequences of 15 Strains of Staphylococcus aureus subsp. aureus Isolated from Foodstuff and Human Clinical Samples

Abstract: The whole-genome sequences of 15 strains of Staphylococcus aureus (10 strains isolated from foodstuff samples in Switzerland and five from human clinical samples) were obtained by Illumina sequencing. Most strains fit within the known diversity for the species, but one (SA-120) possessed a higher G+C content and a higher number of genes than usual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Only one MSSA sequence (SAMN03219992; JXIG01000629.1) was found to harbour see (locus tag QU38_13900). This strain originated from a food sample from Switzerland [ 59 ]. The authors characterized in an earlier study [ 6 ] 29 ST425 isolates from European wildlife (badger, red fox, wild boar, red deer and roe deer) out of which three isolates were positive for see .…”
Section: Resultsmentioning
confidence: 99%
“…Only one MSSA sequence (SAMN03219992; JXIG01000629.1) was found to harbour see (locus tag QU38_13900). This strain originated from a food sample from Switzerland [ 59 ]. The authors characterized in an earlier study [ 6 ] 29 ST425 isolates from European wildlife (badger, red fox, wild boar, red deer and roe deer) out of which three isolates were positive for see .…”
Section: Resultsmentioning
confidence: 99%
“…The production of SEB was confirmed through complementary identifications. We selected the S.aureus strain CCM5757 according to the published presence of the seb gene [ 23 ]. The presence of SEB was proven by using the commercial method of immune-based ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…In Figure 1 , the antibody-based ELISA test shows the presence of SEB as well as a second reproducible signal suggesting SEC presence as well. Our genome analysis [ 23 ] ascribed the seb gene, but not sec , to the corresponding S.aureus strain. This indicates inaccurate ELISA results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported food poisoning outbreaks caused by enterotoxigenic S. aureus, and they were focused on the outbreak investigation, strain genotyping and characterisation of produced SEs [25,[27][28][29]78,79]. Other studies included the identification of different VFs of S. aureus enterotoxigenic strains isolated from foods and from SFP outbreaks by PCR [80,81] with the use of microarray-based methods [82] and analysing the whole genome sequences [83,84]. However, these studies focused on the presence of few VFs or specific staphylococci related to host [85].…”
Section: Discussionmentioning
confidence: 99%